HUBUNGAN PENGGUNAAN ELECTRONIC COMMERCE (E – COMMERCE) DENGAN PEMILIHAN MAKANAN DAN STATUS GIZI PADA MAHASISWA FAKULTAS KESEHATAN UNIVERSITAS MUHAMMADIYAH GRESIK - Putri, Fathmawati Widodo; Supriatiningrum, Dwi Novri; Ariestiningsih, Eka Srirahayu (Ghidza Media Jurnal, 2024)
The use of electronic commerce (e-commerce) has penetrated various fields, one of which is the culinary industry. Improper food selection through e-commerce can impact a person's nutritional status. This study aims to analyze the relationship between e-commerce use, food choices, and nutritional status. Simple random sampling with proportional random sampling was chosen as the method for this research, with a subject size of 88 students from the Faculty of Health at Muhammadiyah University of Gresik. Data collection was carried out using e-commerce usage questionnaires, FFQ questionnaires, and anthropometric measurements. The Spearman correlation test was chosen to analyze the collected data. The results show no significant relationship between the use of e-commerce and food choices, with a p-value of 0.865 for the main food category, 0.700 for the snack category, and 0.305 for the beverage category. There is no significant relationship between the use of e-commerce and nutritional status, with a p-value of 0.709. The conclusion of this research is that there is no significant relationship between the use of e-commerce, food selection, and nutritional status. Suggestions for future research include conducting a recall to determine the intake consumed by students and conducting similar research on various community characteristics.